Manipulation of cytosine methylation does not remove latitudinal clines in two invasive goldenrod species in Central Europe. Issue 1 (26th November 2020) - Eckert, Silvia; Herden, Jasmin; Stift, Marc; Joshi, Jasmin; van Kleunen, Mark
Abstract: Invasive species frequently differentiate phenotypically in novel environments within a few generations, often even with limited genetic variation. For the invasive plants Solidago canadensis and S. gigantea, we tested whether such differentiation might have occurred through heritable epigenetic changes in cytosine methylation. In a 2‐year common‐garden experiment, we grew plants from seeds collected along a latitudinal gradient in their non‐native Central European range to test for trait differentiation and whether differentiation disappeared when seeds were treated with the demethylation agent zebularine. Microsatellite markers revealed no population structure along the latitudinal gradient in S. canadensis, but three genetic clusters in S. gigantea . Solidago canadensis showed latitudinal clines in flowering phenology and growth. In S. gigantea, the number of clonal offspring decreased with latitude. Although zebularine had a significant effect on early growth, probably through effects on cytosine methylation, latitudinal clines remained (or even got stronger) in plants raised from seeds treated with zebularine. Thus, our experiment provides no evidence that epigenetic mechanisms by selective cytosine methylation contribute to the observed phenotypic differentiation in invasive goldenrods in Central Europe.